Satisfaction of pregnant women with prenatal care in basic health units in the Brazilian Midwest (Research, Society and Development, 2020)
Objective: to assess the satisfaction and expectations of pregnant women with prenatal care realized in basic health service in a Brazilian Midwest city. Methods: quantitative cross-sectional study whose sample consisted of 107 pregnant women attended in basic health service, aged 18 years or over and attended at least three prenatal appointments. It was used an instrument with sociodemographic variables and the Brazilian version of Patient Expectations and Satisfaction whit Prenatal Care (PESPC). Statiscal analysis was performed using the independent t test, with statistical significance at 5%. Results: average age of 25.6 (SD=5, 7) years; most married (80, 4%); brown-skinned (62, 6%); housewife (46, 7%); monthly family income up to two minimum wages (43,9%); four to seven years of study (58, 9%); gestational age ranged from 15 to 39 weeks of gestation, more than one pregnancy (38, 3%); one parturition (37, 4%) and one child (37,4%). Satisfaction was associated with complications in the previous pregnancy (p